2000
DOI: 10.1212/wnl.54.10.1886
|View full text |Cite
|
Sign up to set email alerts
|

Practice parameter: Anticonvulsant prophylaxis in patients with newly diagnosed brain tumors [RETIRED]

Abstract: Overview. The Quality Standards Subcommittee seeks to develop scientifically sound, clinically relevant practice parameters for the practice of neurology. Practice parameters are strategies for patient management that assist physicians in clinical decision making. A practice parameter is one or more specific recommendations based on analysis of evidence on a specific clinical problem. These might include diagnosis, symptoms, treatment, or procedure evaluation. American Academy of Neurology (AAN) members have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
266
1
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 793 publications
(283 citation statements)
references
References 73 publications
5
266
1
11
Order By: Relevance
“…Despite lack of evidence showing AED are beneficial, agreement is seen among neurosurgeons with the use of AEDs during the peri-and post-operative period (within 7-14 days of the surgery) as the risk of seizures is the highest during this timeframe [6] . Indeed, this does not contradict the AAN guidelines as they recommend an AED, if started, to be discontinued after 7 days post-surgery if the patient is medically stable and has not experienced a seizure [7] . Overall, the current body of literature does not support the routine use of seizure prophylaxis in patients with primary or secondary brain lesions, whether they undergo neurosurgery or not.…”
Section: Analysis Of the Adherence To Seizure Prophylaxis Guidelinesmentioning
confidence: 89%
“…Despite lack of evidence showing AED are beneficial, agreement is seen among neurosurgeons with the use of AEDs during the peri-and post-operative period (within 7-14 days of the surgery) as the risk of seizures is the highest during this timeframe [6] . Indeed, this does not contradict the AAN guidelines as they recommend an AED, if started, to be discontinued after 7 days post-surgery if the patient is medically stable and has not experienced a seizure [7] . Overall, the current body of literature does not support the routine use of seizure prophylaxis in patients with primary or secondary brain lesions, whether they undergo neurosurgery or not.…”
Section: Analysis Of the Adherence To Seizure Prophylaxis Guidelinesmentioning
confidence: 89%
“…Unless seizures occur, the use of prophylactic anticonvulsants, particularly phenytoin (Dilantin), is not encouraged [18,19]. In combination with radiotherapy, phenytoin may cause Stevens-Johnson syndrome (erythema multiforme major) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for the high incidence of seizures in patients with brain metastases from melanoma, as opposed to other histologies, include the tendency for these metastases to be located in the superficial cerebral cortex rather than at the junction between gray and white matter. The meta-analysis by Glantz et al 34 did not indicate a significant benefit to anticonvulsants in patients with malignant melanoma brain metastases but concluded that further prospective studies of prophylactic anticonvulsants were warranted in this subgroup. The panel consensus is to not start anticonvulsants prophylactically in patients with brain metastases due to any primary cancer, including melanoma (see Variant 3 and Variant 4).…”
Section: Prophylactic Anticonvulsantsmentioning
confidence: 99%
“…A meta-analysis estimated that 15% of patients with brain metastases present with seizures, and most of them are found to have supratentorial lesions. 34 Patients who present with seizures or who develop seizures during therapy should be started on antiseizure medications. Randomized prospective studies have found no significant reduction in the incidence of first seizures in brain tumor patients placed on prophylactic anticonvulsants.…”
Section: Prophylactic Anticonvulsantsmentioning
confidence: 99%
See 1 more Smart Citation